High-power ultrafast Tm-doped fiber lasers for the generation of mid-infrared radiation in the molecular fingerprint region - Heuermann, Tobias; Gebhardt, Martin; Gaida, Christian; Pupeza, Ioachim; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Accessing the molecular fingerprint region between 2 and 20 μm is a key aspect in modern metrology and spectroscopy. While the wavelength range from 2-5 μm can easily be addressed through nonlinear frequency conversion starting from well-matured 1 μm driving lasers, access to the deep mid-IR wavelength regime is difficult. This is, because of the limited transmission of non-oxide crystals (that offer high nonlinearity and good transmission for the aspired mid-IR idler) at the pump wavelength and/or multi-photon absorption. Shifting to a longer pump wavelength relieves these limitations. In this work we present an experiment based on intra pulse difference frequency generation (IPDFG) in GaSe driven by an ultrafast Tm-doped chirped pulse amplifier. This experiment led to an octave spanning mid-IR spectrum, covering the wavelength range between 7.2-16.5 μm (-10 dB width) with 450 mW of average power at 1.25 MHz repetition rate. This result outperforms comparable sources driven at 1 μm wavelength in average power and conversion efficiency, while providing much broader spectral coverage. To further facilitate the use of these promising sources in real-world spectroscopic applications, we have built a nonlinear amplifier, which, based on its compact and robust design is an ideal candidate in this respect. Optimizing the output ultimately led to high pulse quality 50 fs pulses with 250 nJ of pulse energy at 80 MHz of repetition rate and 20 W average output power, exceeding current designs in the anomalous dispersion regime by 1 order of magnitude. It is our ongoing effort to utilize this laser for parametric downconversion. Covering the wavelength regime beyond 5 μm wavelength would make it an enabling technology for next generation spectroscopy, fundamental and life sciences.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber laser; Mid-IR laser; Nonlinear broadening; Nonlinear pulse compression